Perfectionism, the Thin Ideal, and Disordered Eating: Does Internalized Misogyny Play a Role? - Johnson, Shelby (My University, 2014)
Research has consistently shown a relationship between both perfectionism and the internalization of the thin ideal with disordered eating behavior. The relationship between internalized misogyny and disordered eating behavior has not been examined, though internalized misogyny has been shown to be associated with other correlates of disordered eating, including low self-esteem, negative body image, and self-objectification. The purpose of this research study is to determine whether internalized misogyny moderates the relationship between the internalization of the thin ideal and disordered eating behavior, when controlling for the influence of perfectionism. Participants were 318 females ranging in age from 18-64, and contacted via social media to complete an online survey. Hierarchical multiple regression analysis was utilized to examine internalized misogyny’s role as a moderator in the relationship between the internalization of the thin ideal and disordered eating.
Keywords: Education, Educational Psychology.